The impact of anti-Asian racism on routine activities and mental health among Korean American older adults and their caregivers - Hae-Ra Han; Hae-Ra Han; Deborah Min; Deborah Min; Ji-Young Yun; Jin Hui Joo; Hochang Benjamin Lee; Simona Kwon (Frontiers Media S.A., 2023)
IntroductionReported anti-Asian discrimination has been on the rise since the COVID-19 pandemic. Nevertheless, limited research addresses the health impact of perceived anti-Asian racism on Asian Americans, especially among older adults, during COVID-19. To address the gap, we examined how the novel coronavirus pandemic affected Korean American older adults, one of the largest Asian subgroups. Specifically, this study addressed the magnitude of racism or discrimination related to the pandemic and impact of anti-Asian racism on negative mental health symptoms among Korean American older adults and their caregivers.MethodsWe used survey data collected from 175 Korean American older adults with probable dementia and their primary caregivers (female = 62%, mean age = 71 years) who went through eligibility screening for an ongoing randomized controlled trial involving dyads in the Baltimore-Washington and the New York Metropolitan areas (ClinicalTrials.gov Identifier: NCT03909347).ResultsNearly a quarter of the survey sample reported they were fearful for their safety due to anti-Asian racism related to the pandemic. Additionally, 47% of the respondents indicated changes to routine activities due to anti-Asian racism or discrimination related to COVID-19. The most common changes included avoiding walking alone or physical activities outside, followed by avoiding public transportation or leaving the house to go to any public places such as grocery stores, churches, or schools, not carrying out usual social activities, and avoiding going to health care appointments. Multinomial logistic regression revealed that people who reported changes to routine activities were at least five times more likely (adjusted odds ratio = 5.017, 95% confidence interval = 1.503, 16.748) to report negative mental health symptoms than those who did not. Being fearful for their own safety was not associated with experiencing negative mental health symptoms in the survey sample.DiscussionStudy findings indicate that the increased reporting of anti-Asian racism during the COVID-19 pandemic has substantially affected Korean American older adults and their caregivers. The mechanism by which changes to routine activities is related to negative mental health symptoms is unclear, future research is needed to elucidate this pathway. Furthermore, our findings highlight the importance of identifying multi-level strategies to raise awareness of and to mitigate the reported surge of racism.